Incidence of thromboembolism in patients with melanoma on immune checkpoint inhibitor therapy and its adverse association with survival. Issue 1 (12th January 2021) - Sussman, Tamara A; Li, Hong; Hobbs, Brian; Funchain, Pauline; McCrae, Keith R; Khorana, Alok A
Abstract : Background: Thromboembolism (TE) in cancer significantly contributes to morbidity and mortality. Little is known about the incidence of arterial TE (ATE) and venous TE (VTE) in patients with melanoma on immune checkpoint inhibitor (ICI) therapy. Methods: We conducted a retrospective cohort study of patients with melanoma receiving ICI from July 2015 through December 2017 at the Cleveland Clinic. TE, including VTE events of deep venous thrombosis, pulmonary embolism, visceral vein thrombosis, and ATE events of myocardial infarction, stroke, peripheral arterial embolism, or transient ischemic attack after ICI initiation were identified. Overall survival (OS) from ICI initiation was estimated by Kaplan-Meier and Cox hazard models; associations between TE, ICI regimen, and clinical risk factors were evaluated using log-rank test. Results: The study population comprised 228 patients with median age of 65 years (23–91 years), 67% male, and median follow-up of 27.3 months. Pembrolizumab was most commonly used (38.7%), followed by combination of ipilimumab plus nivolumab (29.4%), ipilimumab (20%), and nivolumab (12.3%). Most had stage IV disease (81.1%) and 11% had brain metastases (BM) at treatment initiation. Fifty-one TE events occurred in 47 patients (20.6%), including 37 (16.2%) VTE and 14 (6.1%) ATE. Cumulative incidence of TE after ICI initiation was 9.3% (95% CI: 6.0% to 13.6%) at 6 months, and 16.0% (95% CI: 11.6% to 21.2%) at 12 months. The 6-month and 12-month VTE cumulative incidence rates were higher with combination ICI than single agent (16.7% vs 5.0% and 21.3% vs 9.5%, respectively; p=0.02). Risk factors significantly associated with VTE in multivariate analysis included combination ICI (HR 2.70; 95% CI: 1.28 to 5.70; p=0.009), Khorana Score ≥1 (HR 2.24; 95% CI: 1.06 to 4.74; p=0.03), history of coronary artery disease (HR 2.71; 95% CI: 1.16 to 6.29); p=0.02), and anticoagulation at treatment start (HR 4.14; 95% CI: 1.60 to 10.7; p=0.003). Of patients without BM, OS was worse in patients with TE compared with those without (2-year OS 50.8% vs 71.3%; HR 2.27; 95% CI: 1.36 to 3.79; p=0.002), when adjusted for age and stage. Conclusions: ICI is associated with a high incidence of TE in patients with melanoma, with higher rates with combination therapy; TE is associated with substantial worsening of survival. Further studies are needed to identify pathophysiology, biomarkers, and preventive approaches.